CONCEPTUALIZATION OF DECODABLE BOOKS BASED ON HUMAN SECURITY TO EARLY READER FOR STRENGTHENING OF THE PANCASILA STUDENT PROFILE IN ELEMENTARY SCHOOL - Sani Aryanto; Truly Wangsalegawa; Tri Alida Apriliana; Putri Ayuni Agustina; Meyke Erlianda; Meliyanti Meliyanti (Universitas Majalengka, 2023)
The purpose of this research is to provide a comprehensive picture of the development of decodable books based on human security in an effort to strengthen the Pancasila student profile for students in the Early Readers category in elementary schools (SD). The qualitative approach presented descriptively through library research shows several conceptual findings, such as: (1) Decodable Books Terminology; (2) Characteristics of Decodable Books for Early Readers Category (B1); (3) The Concept of Human Security in SD; (4) Internalization of Pancasila Student Profile Values in the Context of Developing Decodable Books in Elementary Schools The library research was carried out in a comprehensive manner by conducting a meta-analysis of several relevant previous studies, taking inventory of several theoretical studies from various sources, and supporting government policies related to the focus of this study. The results of the study show that book development is explicitly contained in BSKAP No. 030/P/2022 Concerning Guidelines for Leveled Books, although unfortunately this has not been comprehensively discussed. The results of this literature study produce propositions that can be followed up in other, more complex studies. Tujuan penelitian ini adalah untuk memberikan gambaran komprehensif mengenai pengembangan buku ramah cerna berbasis human security sebagai upaya penguatan Pancasila student profilepada siswa kategori Pembaca Awal di Sekolah Dasar (SD). Pendekatan kualitatif yang disajikan secara deskriptif melalui library research menunjukan beberapa temuan yang bersifat konseptual seperti: (1) Hakikat Buku Ramah Cerna; (2) Klasifikasi Buku Ramah Cerna dan Buku Berjenjang; (3) Karakteristik Buku Ramah Cerna untuk Kategori Pembaca Awal (B1); (4) Konsep Human Security di SD; (5) Internaliasi Nilai-Nilai Pancasila student profiledalam Konteks Pengembangan Buku Ramah Cerna di SD. Studi pustaka dilakukan secara komprehensif dengan melakukan metaanalisis pada beberapa penelitian terdahulu yang relevan dan inventarisasi pada beberapa kajian teori dari berbagai sumber serta kebijakan-kebijakan pemerintah yang mendukung terkait fokus kajian ini. Hasil kajian menunjukan bahwa pengembangan buku secara eksplisit terdapat dalam BSKAP No. 030/P/2022 Tentang Pedoman Perjenjangan Buku, walaupun sayangnya belum dibahas secara komprehensif. Hasil studi pustaka ini menghasilkan proposisi yang dapat ditindaklanjuti pada penelitian lainnya yang lebih kompleks.